Mechanisms underlying differential effectiveness of memantine and ketamine in rapid antidepressant responses - Gideons, Erinn S. (National Academy of Sciences, 2014)
Ketamine is an NMDA receptor (NMDAR) antagonist that elicits rapid antidepressant responses in patients with treatment-resistant depression. However, ketamine can also produce psychotomimetic effects that limit its utility as an antidepressant, raising the question of whether the clinically tolerated NMDAR antagonist memantine possesses antidepressant properties. Despite its similar potency to ketamine as an NMDAR antagonist, clinical data suggest that memantine does not exert rapid antidepressant actions for reasons that are poorly understood. In this study, we recapitulate the ketamine and memantine clinical findings in mice, showing that ketamine, but not memantine, has antidepressant-like effects in behavioral models. Using electrophysiology in cultured hippocampal neurons, we show that ketamine and memantine effectively block NMDAR-mediated miniature excitatory postsynaptic currents in the absence of Mg(2+). However, in physiological levels of extracellular Mg(2+), we identified key functional differences between ketamine and memantine in their ability to block NMDAR function at rest. This differential effect of ketamine and memantine extends to intracellular signaling coupled to NMDAR at rest, in that memantine does not inhibit the phosphorylation of eukaryotic elongation factor 2 or augment subsequent expression of BDNF, which are critical determinants of ketamine-mediated antidepressant efficacy. These results demonstrate significant differences between the efficacies of ketamine and memantine on NMDAR-mediated neurotransmission that have impacts on downstream intracellular signaling, which we hypothesize is the trigger for rapid antidepressant responses. These data provide a novel framework on the necessary functional requirements of NMDAR-mediated neurotransmission as a critical determinant necessary to elicit rapid antidepressant responses.